Reading Comprehension in English as Foreign Language from an Action Research Approach - Zapata, Edgar Ivan Castro; Sarracino, David Guadalupe Toledo; Sánchez, Nahum Samperio; Rodríguez, María del Socorro Montaño (Journal of Posthumanism, 2025)
Action research is considered fundamental in several knowledge construction processes, particularly in the education field. For this reason, the present article makes a bibliographic review from different data bases through documentary analysis. This is in order to characterize studies related to the processes of enhancing reading comprehension in English as a foreign language, which use the previously mentioned investigative method. As a result, the information was organized into tables and statistical graphics, which allowed the identification of epistemological, methodological and pragmatic tendencies in relation to categories such as year of publishing, educational stage, used method, type of improved strategy and place where the investigations was developed. Finally, we conclude that action research is a significant tool for the encouraging of the acquisition of English and related competencies at an international level in recent years, in various levels and at professional training levels.